Selection of Strategy Positioning and Formulation Strategies for Improving Business Performance of Bakery XYZ - Siregar, Yigal Allon; Toha, Mohamad (The Indonesian Journal of Business Administration, 2012)
Economic growth will increase competition among companies in industry, and it happen in Bandung area, with current growth in economic and tourism industry also influence competition level in culinary business in Bandung. Bakery XYZ, that already in Bandung since 1991 affected of the current competition in culinary business. Currently Bakery XYZ is facing decreasing sales volume due to increasing competitors. To improve its business performance, is required to analysis Bakery XYZ’s business strategy and analyze Bakery external environment. The approach for analyzing this issue is through societal environment analysis, task environment analysis, STP analysis and acquiring data using questionare to 100 respondents to know their point of view of Bakery XYZ to know whether there is gap between company strategy compare with respondent expectation. After analyzed the datas. Its concluded that Bakery XYZ positioning is too abroad thus make company have no specific strategy for creating distinctive compentency, and in other side company facing high theat of external environment. Based on this conclusion, its recommended for Bakery XYZ to settle its strategic positioning in differentiation strategy in obtrude in product’s taste. Keywords: societal environment analysis, task environment analysis, distinctive competency, strategic positioning, differentiation strategy.